High-performance sensor based on surface plasmon resonance with chalcogenide prism and aluminum for detection in infrared - Jha, Rajan; Sharma, Anuj K (Optics letters, 2009)
A high-accuracy aluminum-based surface plasmon resonance (SPR) chalcogenide sensor is proposed for IR. The structure is based on widely used 2S2G chalcogenide glass with aluminum as the SPR active metal. The angular interrogation method has been used to study the performance of the sensor in terms of intrinsic sensitivity (IS) that includes the width and shifts of the SPR curve for a given refractive index of sensing layer. The IS of Al-based chalcogenide glass sensor is almost 400% more as compared with an Au-based one, which is the most widely used SPR active metal. The oxidation problem of an Al-based SPR sensor has been addressed.